(:unas) unassigned - Pattrawut Chansangiam; Patcharin Hemchote; Praiboon Pantaragphong (My University, 2009)
The purpose of this paper is to develop inequalities for Kronecker products and Hadamard products of positive definite matrices.A number of inequalities involving powers, Kronecker powers, and Hadamard powers of linear combination of matrices are presented.In particular, Hölder inequalities and arithmetic mean-geometric mean inequalities for Kronecker products and Hadamard products are obtained as special cases.
Keywords: null